A magnesium alloy stent material with a coating for in-situ catalytic release of nitric oxide and a method for manufacturing the same
By constructing a copper/dopamine/hexamethylenediamine coating and fluorination treatment on the surface of the magnesium alloy vascular stent, the catalytic activity of endothelial nitric oxide synthase is enhanced, which solves the problem of magnesium alloy stents hindering endothelial cell growth, promotes endothelial cell reconstruction and delays the degradation rate, and improves the biocompatibility and safety of the stent.
Patent Information
- Application Number
- CN202510074142.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-17
- Publication Date
- 2025-10-14
- Estimated Expiration
- 2045-01-17
AI Technical Summary
Existing magnesium alloy vascular stents hinder endothelial cell growth while releasing anti-proliferative drugs, leading to delayed endothelialization and thrombosis. In addition, endogenous nitric oxide donors have low concentrations and short half-lives in the actual pathophysiological microenvironment and cannot provide sufficient catalyst amounts.
A copper/dopamine/hexamethylenediamine coating was constructed on the surface of a magnesium alloy vascular stent, and the anticoagulant molecule bivalirudin was grafted onto it. Cu2+ was used to catalyze the production of nitric oxide gas from endogenous nitric oxide donors, and the catalytic activity of endothelial nitric oxide synthase was enhanced by fluorination treatment and polylipoic acid-arginine coating.
It significantly promotes the reconstruction of endothelial cells, prevents restenosis, slows down the degradation rate of magnesium alloy stents, provides a continuous supply of endothelial nitric oxide, and improves the anti-thrombotic and re-endothelialization capabilities of the stent.
Smart Images

Figure CN119925689B_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the field of surface treatment of magnesium alloy vascular stent materials, and particularly relates to a magnesium alloy vascular stent material with a coating for in-situ catalytic release of nitric oxide and a preparation method thereof. Background Art
[0002] Cardiovascular diseases (CVDs) are currently the leading cause of death and chronic disability. Currently, drug therapy, surgical treatment, and endovascular intervention are the most commonly used methods for treating cardiovascular diseases in clinical practice. In cases where drug therapy is ineffective or arterial stenosis recurs, stent angioplasty becomes an important treatment option. Currently, the main materials used in clinical practice for stents are stainless steel, nickel-titanium alloy, and cobalt-chromium alloy. Since these are all made of non-degradable materials, as permanent foreign bodies in the body, they increase the risk of vascular inflammation and recurrence of atherosclerosis. Therefore, their long-term safety and efficacy remain questionable. Guided by the concept of "intervention without implantation," biodegradable vascular stents have gradually become a focus of attention and a hot topic. Compared with non-degradable stents, biodegradable stents have the unique ability to gradually degrade and eventually disappear after vascular remodeling, effectively avoiding a series of immune rejection issues caused by the long-term and continuous foreign body stimulation of permanent implants.
[0003] Magnesium alloys are considered to be excellent candidate materials for biodegradable implants due to their appropriate mechanical properties, good biocompatibility and inherent bioactivity. Currently, magnesium alloy drug-eluting stents can slow the degradation rate of magnesium stents and have anti-proliferative effects. In 2023, Germany's Biotronik's third-generation magnesium-based drug-eluting coronary stent DREAMS 3G completed a new round of research. The results showed that within 12 months after implantation, 99.3% of the stent beams could be completely absorbed, and the stent could maintain consistent excellent performance regardless of the lesion characteristics. However, drug-eluting magnesium alloy stents still face some difficult clinical problems. The anti-proliferative drugs released by the stent coating will hinder the growth of endothelial cells while effectively promoting smooth muscle cell proliferation, leading to thrombosis and new atherosclerosis caused by delayed endothelialization.
[0004] In response to the problems faced by magnesium alloy vascular stents, researchers have brainstormed and developed a series of cardiovascular stent coatings that mimic the functions of endothelial cells. The healthy endothelium continuously catalyzes L-arginine (referred to as arginine) to produce nitric oxide (NO) through endothelial nitric oxide synthase (eNOS), thereby achieving multiple functions such as inhibiting coagulation, inhibiting excessive proliferation of smooth muscle cells (SMCs), and promoting self-repair of damaged endothelial cells (ECs). Currently, introducing catalysts on the surface of materials to catalyze endogenous NO donors is currently considered a relatively stable strategy. Endogenous nitric oxide donors can be oxidized by some traditional metal ions (such as Fe 2+ 、Zn 2+、Cu 2+ ) catalytically decomposes into nitric oxide gas, in which Cu 2+ The catalytic efficiency of Cu(II) is higher than that of other metal ions. Gao et al. constructed a copper / dopamine / hexamethylenediamine (Cu(II) / DA / HD) coating on the stent surface through a one-step molecular / ion self-assembly method, and then grafted the anticoagulant molecule bivalirudin (BVLD) onto the surface. 2+ It provides glutathione peroxidase catalytic activity, which can be used for sustained and controllable production of nitric oxide gas; the HD molecule provides abundant amine groups, providing a large number of sites for surface grafting of the anticoagulant molecule bivalirudin. In vitro and in vivo results have shown that the nitric oxide gas produced by the synergistic catalysis of bivalirudin improves the stent's ability to resist thrombosis, restenosis, and promote re-endothelialization [Biomaterials, 2020, 248: 119981]. However, the design of nitric oxide coatings that catalyze the production of nitric oxide from endogenous nitric oxide donors often fails to take into account the low local concentration and short half-life of endogenous nitric oxide donors in the actual pathophysiological microenvironment, and therefore may not support sufficient nitric oxide catalysts in the body. Summary of the Invention
[0005] In view of the shortcomings of the existing technology, the present invention provides a magnesium alloy vascular stent material with an in-situ catalytic release of nitric oxide coating and a preparation method thereof based on the pathway of nitric oxide synthesis by endothelial cells, mainly to solve the problems of excessive proliferation and delayed endothelialization faced by current magnesium alloy vascular stents.
[0006] Based on the above purpose, the present invention adopts the following technical solutions:
[0007] A method for preparing a magnesium alloy vascular stent material with a coating that releases nitric oxide in situ catalytically comprises the following steps:
[0008] (1) Take the magnesium alloy vascular stent material, use sandpaper to polish it until the surface is flat and smooth, and then clean it, dry it, and set aside;
[0009] (2) Immersing the magnesium alloy vascular stent material of step (1) in a fluoridation treatment solution, reacting at room temperature for 8 to 48 hours, cleaning, and drying to obtain a magnesium alloy vascular stent material with a magnesium fluoride layer on the surface;
[0010] (3) After heating and melting the lipoic acid powder into liquid, add arginine, continue heating to 130-150°C, stir until the arginine is completely dissolved, and set aside;
[0011] (4) The polylipoic acid-arginine liquid prepared in step (3) is applied to the surface of the magnesium alloy vascular stent material prepared in step (2) and cooled to obtain a magnesium alloy vascular stent material with an in-situ catalytic nitric oxide release coating.
[0012] Preferably, the magnesium alloy vascular stent material in step (1) is ZE21B, WE43, AZ31 or AZ91.
[0013] Preferably, the fluorination treatment liquid in step (2) is at least one of hydrofluoric acid (35-40 wt%), sodium fluoride aqueous solution (0.1M-0.3M) and potassium fluoride aqueous solution (0.1-0.3M).
[0014] Preferably, the molar ratio of lipoic acid to arginine in step (3) is (5-1):1. The melting temperature of the lipoic acid powder in step (3) is 110-130°C.
[0015] Preferably, the polylipoic acid-arginine coating in step (4) is prepared by dip coating or spin coating.
[0016] Preferably, the drying in steps (1) to (4) refers to drying at 40°C to 60°C for 5 to 30 minutes.
[0017] The magnesium alloy vascular stent material with an in-situ catalytic nitric oxide releasing coating prepared by the preparation method.
[0018] The thickness of the magnesium fluoride layer ranged from 0.8 μm to 3.0 μm, and the thickness of the polylipoic acid-arginine coating ranged from 11.0 μm to 16.0 μm.
[0019] Application of the magnesium alloy vascular stent material with the coating for in-situ catalytic release of nitric oxide in the preparation of in vivo implants.
[0020] The technical effect directly brought about by the above technical solution is that the reaction conditions are mild, the operation is simple and safe, and it is easier to be accepted by researchers. The developed polylipoic acid-arginine coating is tightly adhered to the surface of the pretreated magnesium alloy stent based on hydrogen bonding. The polylipoic acid-arginine coating is chemically bonded through salt bridge hydrogen bonds. The arginine fixed in the coating acts as a fuel for synthesizing nitric oxide. Endothelial cells produce nitric oxide through in situ catalysis of endothelial nitric oxide synthase, and lipoic acid acts as an endothelial nitric oxide synthase enhancer, increasing the level of endothelial nitric oxide synthase in endothelial cells and decomposing arginine into nitric oxide, ensuring an adequate supply of in situ nitric oxide. The coating system significantly slows down the degradation rate of the magnesium alloy stent, promotes the reconstruction of natural endothelium, and prevents restenosis. The method of the present invention is highly operational and effective, and provides a new method for the surface coating of magnesium alloy vascular stent materials. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 Schematic diagram of the preparation of the magnesium fluoride / polylipoic acid-arginine coating prepared in Example 1;
[0022] Figure 2SEM images of the magnesium alloy of Example 1 first step, the magnesium fluoride coating prepared in the second step, and the lipoic acid-arginine coating prepared in the third step;
[0023] Figure 3 EDS images of the magnesium fluoride coating prepared in the second step of Example 1, and the lipoic acid-arginine coating prepared in the third step;
[0024] Figure 4 Potentiodynamic polarization curves of the magnesium alloy of Example 1 first step, the magnesium fluoride coating prepared in the second step, and the lipoic acid-arginine coating prepared in the third step;
[0025] Figure 5 Endothelial cell CCK8 test of the blank group of Example 1, the magnesium alloy of Example 1 first step, the magnesium fluoride coating prepared in the second step, and the lipoic acid-arginine coating prepared in the third step, with statistical significant difference (**p<0.01, *p<0.05);
[0026] Figure 6 NO release of the blank group of Example 1, the magnesium alloy of Example 1 first step, the magnesium fluoride coating prepared in the second step, and the lipoic acid-arginine coating prepared in the third step, with statistical significant difference (**p<0.01, *p<0.05);
[0027] Figure 7 Endothelial cell nitric oxide synthase of the blank group of Example 1, the magnesium alloy of Example 1 first step, the magnesium fluoride coating prepared in the second step, and the lipoic acid-arginine coating prepared in the third step, with statistical significant difference (**p<0.01, *p<0.05);
[0028] Note: independent samples were used t - test Significant levels were determined, and differences were considered significant at **p<0.01 and *p<0.05, and *p<0.05 was considered statistically significant. DETAILED DESCRIPTION
[0029] The technical solutions of the present application are further described below in conjunction with examples, but the protection scope of the present application is not limited thereto.
[0030] The magnesium alloy stent materials used in the present application can be purchased from the Material Research Center of Zhengzhou University or commercial channels.
[0031] Example 1:
[0032] A preparation method of a magnesium alloy stent material with an in-situ catalytic release of nitric oxide coating, as shown in Figure 1 , includes the following steps:
[0033] The magnesium alloy vascular stent is made of Mg-2.0Zn-0.5Y-0.5Nd magnesium alloy (brand ZE21B, for the specific preparation process, please refer to patent ZL 201110043303.8).
[0034] Step 1: Pretreatment of magnesium alloy
[0035] The magnesium alloy was cut into cylinders with a diameter of 10 mm and a thickness of 3 mm. The cylinders were polished smooth using 100-mesh, 400-mesh, 800-mesh, and 1000-mesh sandpapers, rinsed with deionized water and anhydrous ethanol, dried at 50°C for 5 min, and set aside.
[0036] Step 2: Surface fluorination treatment of magnesium alloy
[0037] The pretreated ZE21B magnesium alloy sheet was placed in a 24-well plate (with a diameter of approximately 1.5 cm and a well depth of approximately 2 cm, which can hold approximately 3.3 mL of solution);
[0038] Add 2 mL of 40 wt% hydrofluoric acid solution to the wells containing the magnesium alloy sheets, place the 24-well plate in a fume hood, and leave it at room temperature for 12 h;
[0039] The fluorinated ZE21B magnesium alloy sheet was taken out, rinsed with deionized water and anhydrous ethanol in sequence for three cycles to remove the residual reaction solution, and dried at 50°C for 5 min for later use.
[0040] Step 3 Preparation of polylipoic acid-arginine coating
[0041] 10 g of lipoic acid was placed in a 100 mL beaker and heated in an oil bath to 120°C. After melting to a light yellow transparent fluid, arginine was added with a molar ratio of arginine to lipoic acid of 1:2.5. The temperature was continued to rise to 140°C to obtain a polylipoic acid-arginine fluid.
[0042] The polylipoic acid-arginine coating was prepared on the surface of the fluorinated magnesium alloy sample by a dip coating method (maintaining the temperature at 140°C for 2 s) and then cooled.
[0043] The prepared magnesium alloy sample modified with the magnesium fluoride / polylipoic acid-arginine coating is placed in a sample bag and sealed for later use.
[0044] The sample of ZE21B magnesium alloy surface modified with magnesium fluoride / polylipoic acid-arginine coating prepared in Example 1 was subjected to scanning electron microscopy (SEM) observation, energy spectrum (EDS) analysis, potentiodynamic polarization curve analysis, endothelial cell NO test, endothelial cell nitric oxide synthase test and endothelial cell CCK8 test. Figure 1 The experimental results are shown in Figures 2 to 7 shown.
[0045] Figure 1 Figure 1 shows the formation mechanism of the magnesium fluoride / polylipoic acid-arginine coating prepared in Example 1. Lipoic acid self-polymerizes through disulfide bonds to form polylipoic acid. The added arginine and polylipoic acid form high-entropy penalty salt bridge hydrogen bonds, stabilizing the polylipoic acid polymer network. The carboxyl groups of polylipoic acid form dense hydrogen bonds with the magnesium fluoride coating, allowing it to adhere to the fluorinated magnesium alloy surface.
[0046] Figure 2 The SEM images of the samples prepared in Example 1 were gold-sprayed before the morphology was observed. Figure 2 Scratches can be seen on the surface of the magnesium alloy substrate, which are caused by the polishing process. After fluorination, the surface exhibits a relatively smooth morphology, and a dense and uniform fluoride coating can be observed. After coating with polylipoic acid-arginine, the surface morphology of the magnesium alloy vascular stent material is uniform and dense. Furthermore, the thicknesses of the magnesium fluoride coating and polylipoic acid-arginine coating in the polylipoic acid-arginine sample are 2.38 ± 0.27 μm and 13.32 ± 1.93 μm, respectively.
[0047] Figure 3 The following are EDS data for the samples prepared in Example 1. The elemental composition of the magnesium fluoride coating sample is primarily composed of Mg (43.35 wt%) and F (55.74 wt%), corresponding to the magnesium fluoride coating. After preparing the polylipoic acid-arginine coating, the primary elements are C (53.50 wt%), S (27.72 wt%), N (11.24 wt%), and O (7.38 wt%). The C, S, and O elements primarily originate from the lipoic acid, while the N element originates from the arginine.
[0048] The corrosion resistance of the magnesium fluoride / polylipoic acid-arginine coating sample was investigated using an electrochemical workstation. The specific test steps are as follows: the electrochemical workstation is an Interface 1000 model produced by Gamry Electrochemical Company, USA, the electrolyte is Hanks' solution (pH 7.4, 0.14 g / L CaCl2, 0.1 g / L MgCl2·6H2O, 0.1 g / L MgSO4·7H2O, 0.4 g / L KCl, 0.06 g / L KH2PO4, 0.35 g / L NaHCO3, 8.0 g / L NaCl, 0.154 g / L Na2HPO4·12 H2O, 1.0 g / L glucose), and the temperature is 37 °C. All electrochemical measurements were performed in a traditional three-electrode system, in which a platinum sheet was used as the counter electrode, a saturated calomel electrode was used as the reference electrode, and an exposed area of 0.78 cm 2The sample was used as the working electrode. Before the electrochemical test, the sample was immersed in Hanks' solution for 10 min to allow the open circuit potential (OCP) to reach a stable state. The scan rate of the potentiodynamic polarization curve was 1 mV·s -1 The corrosion potential and corrosion current density of the sample can be obtained by Tafel extrapolation. Generally speaking, the lower the corrosion current density, the slower the degradation rate. Figure 4 The potentiodynamic polarization curves of each sample are shown. The corrosion current density of ZE21B magnesium alloy is 1.10 × 10 -5 A / cm 2 After fluorination treatment, the corrosion current density of the magnesium fluoride sample is 1.85×10 -7 A / cm 2 , indicating that the degradation rate of the magnesium alloy matrix was significantly reduced. After modification with polylipoic acid-arginine, the corrosion current density of the coating sample was reduced to 4.62×10 -8 A / cm 2 , further slowing down the degradation rate of the magnesium alloy matrix.
[0049] Human umbilical vein endothelial cells were cultured at 6×10 3 Cells were seeded at a concentration of 100 μL / well onto the bottom of a 24-well plate adhered to the substrate. 400 μL of endothelial cell culture medium was added to each well and the cells were cultured in a constant temperature incubator at 37°C and 5% CO2 for 24 h. Meanwhile, extracts of each sample group were prepared: the samples were transferred to a culture dish and irradiated with ultraviolet light (UV) on the front and back for 60 min, respectively. The samples were then irradiated according to the sample surface area / culture medium volume ratio (1.25 cm 2 Sample extracts were prepared using a 1:1 ratio of 200 μL of culture medium and sample extract per well (1:1 ratio), followed by 200 μL of fetal bovine serum and 2 μL of penicillin-streptomycin solution. This process was repeated every 24 hours, with fresh culture medium added. The culture medium was then removed, and each well was washed with phosphate-buffered saline (PBS). Then, 100 μL of culture medium containing 10% CCK-8 (Solar Biotechnology Co., Ltd., Beijing, China) was added to each well and incubated in a cell culture incubator for 2 hours. The absorbance of each sample at 450 nm was measured using a microplate reader (BIO-RAD680, Bio-Rad, USA). In addition, at the time points of 24 h and 72 h of culture, the old culture medium removed from the cells was used to detect the content of NO and endothelial nitric oxide synthase. The specific steps were as follows: (1) The amount of NO generated was evaluated using a NO detection kit (Biyuntian Biotechnology Co., Ltd., China). The released NO was easily oxidized to NO2 -, quickly forming a pink diazo compound with Griss reagent. The test process was carried out strictly in accordance with the manual of the NO detection kit, and the NO detection wavelength was 540nm. (2) Use the ELISA kit (Elerite Biotechnology Co., Ltd.) to test the endothelial cell nitric oxide synthase content. Add 100 μL of sample group culture medium to the enzyme-labeled plate, incubate at 37℃ for 90 minutes, shake off the liquid in the well, add 100 μL of biotinylated antibody working solution to the well, incubate at 37℃ for 1 hour, shake off the liquid in the well, wash the plate 3 times, pat dry on clean absorbent paper, add 100 μL of HRP enzyme conjugate working solution to each well, incubate at 37℃ for 30 minutes, shake off the liquid in the well, wash the plate 5 times, add 90 μL of substrate color development solution to each well, incubate at 37℃ in the dark for 15 minutes, add 50 μL of stop solution to each well, stop the reaction, and immediately measure the absorbance of each well at a wavelength of 450 nm using an enzyme reader. For details, refer to the ELISA kit steps.
[0050] like Figure 5 The results of the endothelial cell proliferation assay for all samples are shown. Higher absorbance values indicate greater endothelial cell proliferation. After 24 hours of culture, the absorbance values of the blank control, ZE21B magnesium alloy, and magnesium fluoride-coated samples ranged from 0.48 to 0.50, while the absorbance value of the polylipoic acid-arginine coating group was 0.53 ± 0.014, indicating that the polylipoic acid-arginine coating promoted the initial adhesion and proliferation of endothelial cells. After 72 hours of culture, the absorbance values of all sample groups increased significantly. Notably, the absorbance values of the ZE21B magnesium alloy (1.24 ± 0.01) and magnesium fluoride-coated groups (1.17 ± 0.021) were lower than those of the blank control (1.25 ± 0.018), indicating a negative impact on endothelial cell growth. In contrast, the absorbance value of the polylipoic acid-arginine coating group was 1.30±0.02, which exceeded that of the blank control group, ZE21B magnesium alloy group and magnesium fluoride coating group, indicating that it has the ability to promote endothelial cell proliferation. This is attributed to the polylipoic acid-arginine coating system significantly promoting the release of NO, thereby promoting the self-repair of damaged endothelial cells.
[0051] As Figure 6The results of the NO release test showed that throughout the culture period, the polylipoic acid-arginine coating group released significantly higher levels of NO than the other groups: 1-day blank group (0.50±0.005), ZE21B magnesium alloy (0.52±0.006), magnesium fluoride coating (0.54±0.01), and polylipoic acid-arginine coating (0.58±0.015); 3-day blank group (0.54±0.01), ZE21B magnesium alloy (0.54±0.015), magnesium fluoride coating (0.57±0.005), and polylipoic acid-arginine coating (0.63±0.015). This indicates that the LBL coating stimulated EC to release more NO, demonstrating its superiority over the other sample groups. These results are attributed to the fact that the lipoic acid and arginine contained in the polylipoic acid-arginine coating act as an enhancer of endothelial nitric oxide synthase and a fuel for NO synthesis, respectively, thereby promoting NO release.
[0052] In order to verify the above conclusion, the content of endothelial nitric oxide synthase was quantitatively detected. Figure 7 The data show the content of endothelial nitric oxide synthase in all sample groups. The content of endothelial nitric oxide synthase in the polylipoic acid-arginine coating group was as high as 397.25±8.94 pg / mL (24h) and 4577.68±357.63 pg / mL (72h) during the culture period, which was much higher than that in other groups. This shows that lipoic acid significantly increased the activity of endothelial nitric oxide synthase, released more NO, and promoted the proliferation and growth of endothelial cells.
[0053] The above description is only part of the embodiments of the present invention. For ordinary technicians in this technical field, several improvements and substitutions can be made without departing from the principles of the present invention. These improvements and substitutions should also be considered as the scope of protection of the present invention.
Claims
1. A method for preparing a magnesium alloy vascular stent material with an in-situ catalytic nitric oxide release coating, characterized in that: The following steps are involved: (1) Take the magnesium alloy vascular stent material, use sandpaper to polish it until the surface is flat and smooth, and then clean it, dry it, and set aside; (2) Immersing the magnesium alloy vascular stent material of step (1) in a fluoridation treatment solution, reacting at room temperature for 8 to 48 hours, cleaning, and drying to obtain a magnesium alloy vascular stent material with a magnesium fluoride layer on the surface; (3) After heating and melting the lipoic acid powder into liquid, add arginine, continue heating to 130-150°C, stir until the arginine is completely dissolved, and set aside; the molar ratio of lipoic acid to arginine is (5-1):1; (4) The polylipoic acid-arginine liquid prepared in step (3) is applied to the surface of the magnesium alloy vascular stent material prepared in step (2) and cooled to obtain a magnesium alloy vascular stent material with an in-situ catalytic nitric oxide release coating.
2. The preparation method according to claim 1, wherein The magnesium alloy vascular stent material described in step (1) is ZE21B, WE43, AZ31 or AZ91.
3. The preparation method according to claim 1, wherein The fluorination treatment liquid described in step (2) is at least one of a 35-40 wt% hydrofluoric acid solution, a 0.1 M-0.3 M sodium fluoride aqueous solution, and a 0.1-0.3 M potassium fluoride aqueous solution.
4. The preparation method according to claim 1, wherein The melting temperature of the lipoic acid powder in step (3) is 110-130°C.
5. The preparation method according to claim 1, wherein The polylipoic acid-arginine coating described in step (4) is prepared by dip coating or spin coating.
6. A magnesium alloy vascular stent material with a coating that releases nitric oxide in situ catalytically, prepared by the preparation method according to any one of claims 1 to 5.
7. The magnesium alloy vascular stent material with an in-situ catalytic nitric oxide release coating according to claim 6, characterized in that: The thickness of the magnesium fluoride layer ranged from 0.8 μm to 3.0 μm, and the thickness of the polylipoic acid-arginine coating ranged from 11.0 μm to 16.0 μm.
8. Use of the magnesium alloy vascular stent material with an in-situ catalytic nitric oxide releasing coating according to claim 6 or 7 in the preparation of an in vivo implant.
Citation Information
Patent Citations
Mg-Zn-Y-Nd alloy for novel biodegradable vascular stents and preparation method thereof
CN102220529B
Degradable polymer coating support with sequential response function, and making method thereof
CN104107459A
Method for preparing copper polylipoate coating on surface of cardiovascular and cerebrovascular stent material and cardiovascular and cerebrovascular stent material containing coating
CN115581808A